The Association of Polyunsaturated Fatty Acid δ-5-Desaturase Activity with Risk Factors for Type 2 Diabetes Is Dependent on Plasma ApoB-Lipoproteins in Overweight and Obese Adults. Issue 1 (10th December 2018) - Lamantia, Valérie; Bissonnette, Simon; Provost, Viviane; Devaux, Marie; Cyr, Yannick; Daneault, Caroline; Rosiers, Christine Des; Faraj, May
ABSTRACT: Background: δ-5 and δ-6 desaturases (D5D and D6D) catalyze the endogenous conversion of n–3 (ω-3) and n–6 (ω-6) polyunsaturated fatty acids (PUFAs). Their activities are negatively and positively associated with type 2 diabetes (T2D), respectively, by unclear mechanisms. Elevated plasma apoB-lipoproteins (measured as plasma apoB), which can be reduced by n–3 PUFA intake, promote T2D risk factors. Objective: The aim of this study was to test the hypothesis that the association of D5D and D6D activities with T2D risk factors is dependent on plasma apoB. Methods: This is a pooled analysis of 2 populations recruited for 2 different metabolic studies. It is a post hoc analysis of baseline data of these subjects [ n = 98; 60% women (postmenopausal); mean ± SD body mass index (in kg/m 2 ): 32.8 ± 4.7; mean ± SD age: 57.6 ± 6.3 y]. Glucose-induced insulin secretion (GIIS) and insulin sensitivity (IS) were measured using Botnia clamps. Plasma clearance of a high-fat meal (600 kcal/m 2, 66% fat) and white adipose tissue (WAT) function (storage of 3 H-triolein-labeled substrate) were assessed in a subpopulation ( n = 47). Desaturase activities were estimated from plasma phospholipid fatty acids. Associations were examined using Pearson and partial correlations. Results: While both desaturase activities were positively associated with percentage of eicosapentaenoic acid, only D5D was negatively associated with plasma apoB ( r = −0.30, P = 0.003). Association of D5D activity with second-phase GIIS ( r = −0.23, P = 0.029), IS ( r = 0.33, P = 0.015, in women) and 6-h area-under-the-curve (AUC6h ) of plasma chylomicrons (apoB48, r = −0.47, P = 0.020, in women) was independent of age and adiposity, but was eliminated after adjustment for plasma apoB. D6D activity was associated in the opposite direction with GIIS ( r = 0.24, P = 0.049), IS ( r = −0.36, P = 0.004) and AUC6h chylomicrons ( r = 0.52, P = 0.004), independent of plasma apoB. Both desaturases were associated with plasma interleukin-1-receptor antagonist (D5D: r = −0.45, P < 0.001 in women; D6D: r = −0.33, P = 0.007) and WAT function (trend for D5D: r = 0.30, P = 0.05; D6D: r = 0.39, P = 0.027) independent of any adjustment. Conclusions: Association of D5D activity with IS, lower GIIS, and plasma chylomicron clearance is dependent on plasma apoB in overweight and obese adults.